2020
DOI: 10.1007/s42729-020-00228-8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Covariates to Assess the Spatial Variability of Saturated Soil Hydraulic Conductivity Using Robust Cokriging at the Watershed Scale

Abstract: The mapping of saturated soil hydraulic conductivity (K Sat) is essential to understanding soil water dynamics and is a sensitive input in hydrological modeling. The objectives of this study were to provide a reference for the selection of soil hydrology and other environmental attributes that can be used as covariates for estimating K Sat and to compare the efficiency of univariate ordinary kriging versus ordinary robust cokriging, using selected soil hydrology and environmental attributes. Data sets were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 59 publications
(64 reference statements)
1
0
0
Order By: Relevance
“…Villarreal et al (2020) concluded the same, but indicate that in soils with low clay content the differences between tillage systems disappear. Alletto and Coquet (2009) found a gradual decrease of K s through time, and in general lower values in the wheel track than outside, depending on variations of coarse porosity and bulk density, as was observed by Soares et al (2020) at a large-scale approach. Wahl et al (2004) found a correlation of the infiltration values with the macroporosity depending on the dynamic of CT in time, being the initial mechanical loosening and subsequent soil settlement the main factors during the season.…”
Section: Unsaturated and Saturated Hydraulic Conductivitysupporting
confidence: 53%
“…Villarreal et al (2020) concluded the same, but indicate that in soils with low clay content the differences between tillage systems disappear. Alletto and Coquet (2009) found a gradual decrease of K s through time, and in general lower values in the wheel track than outside, depending on variations of coarse porosity and bulk density, as was observed by Soares et al (2020) at a large-scale approach. Wahl et al (2004) found a correlation of the infiltration values with the macroporosity depending on the dynamic of CT in time, being the initial mechanical loosening and subsequent soil settlement the main factors during the season.…”
Section: Unsaturated and Saturated Hydraulic Conductivitysupporting
confidence: 53%